Individual Factors Contributing to Nausea in First-Time Chemotherapy Patients: A Prospective Cohort Study - Meissner, Karin; Talsky, Nicola; Olliges, Elisabeth; Jacob, Carmen; Stötzer, Oliver J.; Salat, Christoph; Braun, Michael; Flondor, Raluca (Frontiers in Pharmacology, 2019)
Objective: The expectation of developing side effects can enhance the likelihood to develop them – a phenomenon referred to as nocebo effect. Whether nocebo effects can be reduced by lowering negative expectancies, is not clear. The aim of this prospective study was to learn more about the factors contributing to nausea expectancy and their potential role in actual occurrence of nausea in patients undergoing chemotherapy for the first time in their life. Methods: Patients scheduled for moderately emetogenic chemotherapeutic regimens filled in questionnaires to assess state anxiety and quality of life and to rate the expectancy of nausea as a side effect of chemotherapy. Patient diaries were used to monitor the severity of post-chemotherapy nausea in the four days following chemotherapy administration. Bivariate analyses complemented by multiple regression analyses were performed to identify the relationship between nausea expectation and nausea occurrence. Results: 121 female patients (mean age 53 years) with completed questionnaires were included in the analyses. The majority of the patients had a diagnosis of breast cancer (86%). The two main sources for nausea expectancy were positive history of nausea in other situations and state anxiety. Patients with high expectancy levels (first quartile) experienced greater nausea than those with lower expectancy levels. Bivariate analyses revealed a weak but non-significant association between nausea expectation and post-chemotherapy nausea. When controlling for age, type of cancer, history of nausea, state and trait anxiety, and global quality of life, positive history of nausea (OR = 2.592; 95% CI, 1.0 to 6.67; p < 0.05), younger age (OR = 0.95; 95% CI, 0.92 to 0.99; p < 0.05), and a lower quality of life (OR = 0.97; 95% CI, 0.94 to 1.0; p < 0.05), but not nausea expectancy (OR = 1.014; 95% CI, 0.51 to 2.02; p = 0.969), predicted the occurrence of post-chemotherapy nausea. Conclusions: In this female cohort, younger patients with lower initial quality of life and a positive history of nausea were at higher risk to develop nausea after first time chemotherapy. These patients may benefit from psychological co-interventions that aim to enhance quality of life.